Community-based Approach to Empower People with Disabilities - Anif Fatma Chawa; Moch Hisyam Putra; Dano Purba (The Center for Disability Studies and Services Brawijaya University, 2021)
This article seeks to understand the empowerment issues of persons with disabilities. Various development programs have been implemented to reduce stigma, prejudice and stereotypes that impede persons with disabilities from having greater access to education, employment or the labor markets and public services. However, research findings showed that many interventions and strategies to address disability issues focus more on individual or medical models. As a consequence, public stigma and social exclusion of persons with disabilities continue to occur, preventing them from participating in various activities in the society including in the tourism sector. The purpose of this study is to identify social reasons that lead to exclusion and lack of empowerment, as well as to establish programs at the community level to increase the engagements of persons with disabilities in tourist attractions and tourist destinations in Malang. The result of the study shows that the insufficient skills and knowledge of the community members of Desa Kalisanga (nicknamed Kampung Cempluk) in communicating and interacting with persons with disabilities cause the lack of awareness in regard to disability issues. Using macro perspective, this study exhibits community-based approach which requires participation of community members in the planning and organizing an inclusive arts and music festival in Kampung Cempluk. The community was successfully provided various accessibility facilities needed by persons with disabilities to participate, both attending and performing at the festival. This study shows that community-based approach could be employed as a model or strategy to empower persons with disabilities by providing them with equal opportunities to participate in tourist attractions or other activities in the society and wider access to tourist destinations and other public facilities.